Makroekonomické důsledky fiskální decentralizace regulace výpůjček nižších vládních úrovní - Provazníková, Romana (Univerzita Pardubice, 2004)
The paper discusses the constraints that a high degrees of decentralization places on the central government's ability to carry out is traditional stabilisation functions. The literature of fiscal federalism pays relatively little emphasis on the effects of decentralisation on macroeconomic management, although policymakers worldwide increasingly have to grapple these effects. The paper describes various country experiences in this area.
Keywords: fiskální decentralizace; veřejné finance; makroekonomický vývoj